(untitled) (Journal of Human Sciences, 2018)
The existentialism was a philosophy developed by the Danish philosopher SørenKirkgard (1813-1855), who relied on self as the basis of his philosophy, and he represents the faithful wing of existentialism. One of the most prominent representatives of this atheist wing of existentialism was Martin Heidegger (1889-1916) and Jean Paul Sartre (1905-1980). The existentialism in contemporary Arab philosophy was presented by Abdurrahman Badawi after he was influenced by the ideas and views of the existential philosophers. Like other existentialists, Abdurrahman Badawi focuses on the living being with all his feelings and emotions, which is in the world we see daily, not that which is the result of mental developments. Existentialism rebelled against everything that is universal, and sanctifies the individual’s right, because existence - according to existentialism - is in essence the existence of (the self) that makes all things and the whole world a tool for theexistentialism.